EXTRACTION OF COPPER ELECTROLYTICALLY BY USING SOLID MIXTURE OF CuFeS2 AND CaCO3 (CHALCOPYCA) AS ANODE - Agus Kuncaka; Eko Sugiharto; Yasinta Endah Nastiti (Universitas Gadjah Mada, 2005)
Study on a new road of copper electroextraction to make use the solid mixture of CuFeS2 and CaCO3 as anode has been done. The aim of these research was to determine reaction kinetic and faradic efficiency of anodic copper dissolution and catodic copper precipitation. A solid mixture of CuFeS2 and CaCO3 at weight ratio 9:1 was functioned as anode. Electrolysis was carried out at 1.5 mA by varying times of 30,60,120, and 240 minutes in Na2SO4 0.5 M + H2SO4 0.01 M electrolyte. The quantity of copper at the electrolyte and cathode was analyzed by Atomic Absorption Spectrophotometer (AAS). The result of these research showed that copper was deposited in the cathode simultaneously with anodic dissolution. The kinetic of copper dissolution follow zero order with rate constant of 5.10-6 mg/second. The faradic efficiency of copper dissolution and precipitation for those various time respectively were 17.31%; 14.00%; 11,16%; 62.31%; and 1.60%; 8.61%; 7.59%; 60.63%.